Attention and Memory Neuropsychological profile in the Colombian armed - Luna Hernández, José Alberto (2018)
This study sought to determine the neuropsychological performance of attention and memory in victims of forced displacement due to the Colombian armed conflict. The methodology used was of comparative descriptive type, with a quantitative paradigm. The sample was of 20 people distributed in group A (9 people with PTSD) and group B (11 people without PTSD). Participants were evaluated with NEUROPSI battery (attention and memory). Results show that the group with PTSD had a lower performance compared to the group without PTSD in attention, while in memory the group with PTSD showed a better performance of the tasks; the existing difficulties in group A can be related to PTSD as an influential variable in the appearance of cognitive deficits.